Quantum Hall effect in p-Ge/Ge1-xSix heterostructures with low hole mobility: Электронные свойства низкоразмерных систем - Arapov, Yu.G.; Harus, G.I.; Karskanov, I.V.; Neverov, V.N.; Shelushinina, N.G.; Yakunin, M.V.; Kuznetsov, O.A.; Ponomarenko, L.; Visser, A. de (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The apparent insulator—quantum Hall—insulator (I—QH—I) transition for filling factor n = 1has been investigated in p-type Ge/Ge1–xSix heterostructures with eFt / ħ ≈ 1. Scaling analysis is carried out for both the low- and high-field transition point. In low magnetic fields wct < 1 pronounced QH-like peculiarities for n = 1 are also observed in both the longitudinal and Hall resistivities. Such behavior may be evidence of a localization effect in the mixing region of Landau levels and is inherent for two-dimensional structures in a vicinity of the metal—insulator transition.